PERANCAH TULANG BERBASIS KOMPOSIT HIDROKSIAPATIT/SILIKA MELALUI METODE 3D-PRINTING: SEBUAH KAJIAN NARATIF - Evi . J; Siska Oktaviyani; Mahjur Mahjur; Fitri Afriani (Prodi Fisika FST UNJA, 2020)
Bone scaffolding is an alternative solution developed to assist the bone therapy process. One of the materials with good biocompatibility and can be applied as a scaffold is hydroxyapatite (HAp). The development of HAp/silica composites aims to improve various characteristics of pure HAp-based scaffolding. In this article, a narrative review is conducted regarding the use of cockle shells as a source of calcium in the synthesis of HAp and tin tailings sand as a silica source. Various HAp synthesis and silica purification methods were compared to obtain the optimal HAp/silica composites method. Furthermore, this article also describes the potential use of 3D-printing technology in scaffolding fabrication. It is because 3D-printing technology has a promising prospect for producing scaffolding with complex structures precisely, efficiently, and quickly to meet patient needs. Also, we explained the challenges of applying 3D-printing technology to provide input for related research in the future.